PENGARUH LINGKUNGAN KERJA, KEPUASAN KERJA, DAN KOMPENSASI TERHADAP PRODUKTIVITAS KARYAWAN PT. SEMBILAN PILAR UTAMA - Utama, Willi Bima Maulana; Arianto, Tezar (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2024)
This research is a quantitative approach. The method used in this research is descriptive method. The population in this study are all employees at PT. Nine Main Pillars of Kepahiang totaling 42 people. The data collection method used here includes four types including interviews, observation, literature studies, questionnaires. The data obtained in this study will be processed using SPSS 20 software. The data analysis technique uses quantitative analysis. Based on the results of the study, there is an influence of the work environment (X1) on employee productivity (Y) PT. The Nine Main Pillars with tsig values ​​<α (0.001<0.05) and tcount > ttable (2.571> 1.68195) thus Ho is rejected and Ha is accepted. From the significance value obtained that the variable X1 has an effect on employee productivity (Y). There is an effect of compensation (X3) on employee productivity (Y) PT. The Nine Main Pillars with tsig values ​​<α (0.003<0.05) and tcount > ttable (2.571> 1.68195) thus Ho is rejected and Ha is accepted. From the significance value obtained that the variable X3 has an effect on employee productivity (Y). There is an influence that the independent variables jointly affect the dependent variable where the Fsig value <α 0.05 and Fcount > F table (16.373> 2.83) Keywords : Work Environment, Job Satisfaction, Compensation, Employee Productivity.